Electrochromic smart windows with co-intercalation of cations and anions for multi-band regulations - Jiawei Sun; Zhe Chen; Renfu Zhang; Menghan Yin; Ying Zhu; Jiacheng Hu; Qinqi Zhou; Peipei Shao; Qingjiao Huang; Dongyun Ma; Rui-Tao Wen; Jinmin Wang (Nature Communications)
Abstract Electrochromic technology has been considered as an energy-efficient approach to reduce the energy consumption in buildings and vehicles. Studies of electrochromic devices (ECDs) have so far focused mainly on control of cations (for example, H+, Li+, Na+, K+, and Zn2+, etc), while anions were rarely considered. Here, X-ray photoelectron spectroscopy (XPS) provides direct evidence that the transformation of Prussian blue (PB) to Prussian green (PG) occurs due to an anion intercalation process, in addition to the cation intercalation-induced switching between PB and Prussian white (PW). Co-intercalation of cations and anions is found in an ECD combining Nb18W16O93 and PB as complementary electrochromic layers: cations (for example, K+) insertion into Nb18W16O93 leads to its colored state and anions (for example, Cl−) insertion into PB forms PG. Benefiting from the co-intercalation of both cations and anions, the Nb18W16O93/PB based ECD can achieve diverse color and spectral modulations while maintaining excellent performance retention, thanks to the charge balance design. The concept of co-intercalation of cations and anions in an ECD provides a new approach to the development of next-generation high-performance ECDs.